Regional Volvme Tables for Poplar (Populus deltoides) (Based on Data of U.P.) - Lohani, D. N.; Sharma, R. P. (Indian Forester, 1977)
Volume tables of poplar have been prepared by the method of linear regression using a computer. The models used are V=a+b D2H and âˆšV=a+b D. Both equations give highly significant results. Tables for the total wood have been given.